Protoplast Fusion between Indonesian Citrus maxima (Burm.) Merr. and Citrus reticulata L.: A Preliminary Report - Dyah Retno Wulandari; Agus Purwito; Slamet Susanto; Ali Husni; Tri Muji Ermayanti (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Protoplast fusion is a useful technique for citrus genetic improvement. Establishment of protoplast technology could produce triploid seedles citrus and new citrus genetic combination. The aim of this research was to establish protoplast isolation, protoplast fusion between pummelo ‘Nambangan’ (Citrus maxima) and keprok ‘Garut’ (C. reticulata), and its protoplast culture. Protoplasts were isolated from leaves of in vitro seedlings of pummelo ‘Nambangan’ and embryogenic callus of keprok ‘Garut’ with two different compositions of enzymes. The results showed that optimum enzymes compositions for cells mesophyl wall degradation were consisted of 0.5 % Onozuka cellulase RS10, 0.5 % Macerozyme R10 and 0.1 % Pectolyase Y23. Optimum enzymes composition for callus embryogenic cells wall degradation were 0.5 % Onozuka cellulase RS10 added with 0.5 % Macerozyme R10. Protoplast fusion was conducted with PEG-mediated. Protoplast mixture were incubated in 40 % PEG for 8-10 min and after that could be observed 40.6 % of unfused protoplasts, 4.6 % of homofused mesophyl protoplasts, 28.2 % of homofused callus protoplasts, 7.8 % of heterofused and 9.6 % of multifused protoplasts from mesophyl and callus. Cells divided at the first week and began to form cell colonies afterwards in liquid culture.